Contribution of anthropogenic aerosol and greenhouse gas emissions to changes in summer upper-tropospheric thermal contrast between Asia and the North Pacific - Peilin Li; Botao Zhou; Dapeng Zhang; Wenxin Xie; Zhicong Yin; Yanyan Huang; Bo Sun; Qiaohong Sun (npj Climate and Atmospheric Science)
Abstract Change of zonal thermal contrast in the upper troposphere (ZTUT) between Asia and the North Pacific is a highly concerned issue, as it profoundly influences the Northern hemispheric climate. However, the physical reasons, particularly the anthropogenic influences on the ZTUT change are not well understood. Here, we show that increased aerosols and greenhouse gases tend to weaken the summer Asian-Pacific ZTUT, through affecting radiation processes over the Tibetan Plateau and altering moist enthalpy advections over the North Pacific, respectively. Under the present climate, aerosol variations play a leading role in the trend change of summer ZTUT from a deceasing to an increasing pattern in the mid-1980s. These decreasing and increasing trends are, respectively, enhanced and attenuated by greenhouse gas emissions. Toward the end of this century under the SSP2–4.5 scenario, continuous increases in greenhouse gases are expected to become the dominant contributor for projected weakening of summer ZTUT, with the rate offset by decreases in aerosols.